Direct and indirect effects of early-life environment on lifetime fitness of bighorn ewes. Issue 1870 (10th January 2018) - Pigeon, Gabriel; Pelletier, Fanie
Abstract : Cohort effects, when a common environment affects long-term performance, can have a major impact on population dynamics. Very few studies of wild animals have obtained the necessary data to study the mechanisms leading to cohort effects. We exploited 42 years of individual-based data on bighorn sheep to test for causal links between birth density, body mass, age at first reproduction (AFR), longevity and lifetime reproductive success (LRS) using path analysis. Specifically, we investigated whether the effect of early-life environment on lifetime fitness was the result of indirect effects through body mass or direct effects of early-life environment on fitness. Additionally, we evaluated whether the effects of early-life environment were dependant on the environment experienced during adulthood. Contrary to expectation, the effect on LRS mediated through body mass was weak compared to the effects found via a delay in AFR, reduced longevity and the direct effect of birth density. Birth density also had an important indirect effect on LRS through reduced longevity, but only when adult density was high. Our results show that the potential long-term consequences of a harsh early-life environment on fitness are likely to be underestimated if investigations are limited to body mass instead of fitness at several life stages, or if the interactions between past and present environment are ignored.